Gomisin M2 Inhibits Mast Cell-Mediated Allergic Inflammation via Attenuation of FcεRI-Mediated Lyn and Fyn Activation and Intracellular Calcium Levels - Dhakal, Hima; Lee, Soyoung; Kim, Eun-Nam; Choi, Jin Kyeong; Kim, Min-Jong; Kang, Jinjoo; Choi, Young-Ae; Baek, Moon-Chang; Lee, Byungheon; Lee, Hyun-Shik; Shin, Tae-Yong; Jeong, Gil-Saeng; et al. (Frontiers in Pharmacology, 2019)
Mast cells are effector cells that induce allergic inflammation by secreting inflammatory mediators. Gomisin M2 (G.M2) is a lignan isolated from Schisandra chinensis (Turcz.) Baill., exhibiting anti-cancer activities. We aimed to investigate the anti-allergic effects and the underlying mechanism of G.M2 in mast cell-mediated allergic inflammation. For the in vitro study, we used mouse bone marrow-derived mast cells, RBL-2H3, and rat peritoneal mast cells. G.M2 inhibited mast cell degranulation upon immunoglobulin E (IgE) stimulation by suppressing the intracellular calcium. In addition, G.M2 inhibited the secretion of pro-inflammatory cytokines. These inhibitory effects were dependent on the suppression of FcεRI-mediated activation of signaling molecules. To confirm the anti-allergic effects of G.M2 in vivo, IgE-mediated passive cutaneous anaphylaxis (PCA) and ovalbumin-induced active systemic anaphylaxis (ASA) models were utilized. Oral administration of G.M2 suppressed the PCA reactions in a dose-dependent manner. In addition, G.M2 reduced the ASA reactions, including hypothermia, histamine, interleukin-4, and IgE production. In conclusion, G.M2 exhibits anti-allergic effects through suppression of the Lyn and Fyn pathways in mast cells. According to these findings, we suggest that G.M2 has potential as a therapeutic agent for the treatment of allergic inflammatory diseases via suppression of mast cell activation.